Effect of waters sources on the concentration of some phenolic compounds in the vegetative part of alfalfa plant. - admin, Abdulmoneim M.A.K.; Saied, Salah M. (Al-Qadisiyah Journal of Pure Science, 2017)
This study was conducted during 2008-2011 to detect the impact of water sources on the content of some phenolic compounds in the vegetative part of alfalfa plant. Water sources includes (groundwater, rivers, water receding, and household waste) to irrigate alfalfa plants. Results demonstrated significant differences among the water sources in characteristics. The highest value of average electrical conductivity 3072 Î¼mhos/cm for the groundwater, and the lowest value was 278 Î¼mhos/cm for river water . Concentration of cation and anion are highest in underground water except potassium and phosphorus ions which were highest in household water. Classification of water types used for irrigation was done by American laboratory for salinity(LSA)Í¾ and rank of C4-S1 for underground and receding while household water and river water ranked C3-S1 and C2-S1, respectively. Phenolic compounds have been isolated from Alfalfa plant tissues by the use of HPLC were: Gallic acid, Chlorogenic acid, Syringic acid, Daidzein, Luteolin, Apigenin, Flavone, P-Hydroxybenzoic acid.